(untitled) (Canadian Medical Education Journal, 2018)
You find me, Sprawled across the cold, dark asphalt. Incoherent, incompetent, "incapable". Hypotensive, bradycardic, cyanotic. Overdosed. For a moment, you pity me. So young, likely to succumb to the effects of the chemical concoction that I consciously forced through my veins. Overdosed. Your pity subsides. It makes way for disgust. For judgement. How could I have elected to end up this way? Overdosed. You walk around my limp, virtually lifeless body. Assessing the patient, As you have spent an eternity learning to do. Through it all, my eyes stare right through you. Overdosed. Perhaps, fentanyl isn’t solely responsible for my state. Perhaps, it was neglect, a faulty system. But, judge as you may, I overdosed. Help.